2011
DOI: 10.1016/j.taap.2010.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manganese on tyrosine hydroxylase (TH) activity and TH-phosphorylation in a dopaminergic neural cell line

Abstract: Manganese (Mn) exposure causes manganism, a neurological disorder similar to Parkinson's disease. However, the cellular mechanism by which Mn impairs the dopaminergic neurotransmitter system remains unclear. We previously demonstrated that caspase-3-dependent proteolytic activation of protein kinase C delta (PKCδ) plays a key role in Mn-induced apoptotic cell death in dopaminergic neurons. Recently, we showed that PKCδ negatively regulates tyrosine hydroxylase (TH), the rate-limiting enzyme in dopamine synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 48 publications
6
44
1
Order By: Relevance
“…First, olfactory Mn instillation significantly down-regulated TH by 78% in iron-adequate rats ( Figure 5A; P< 0.001) and by 70% in iron-deficient rats (P< 0.001; n = 4 per group), which is in agreement with Zhang et al [42], who showed that chronic manganese exposure (0.1-1 µM for 24 h) induced a dose-dependent decrease in TH activity of dopaminergic neuronal cell line. Sriram et al [43] also reported that rats exposed to aerosolized welding fumes (manual metal arc-hard surfacing; containing high Mn) of 0.5 mg/rat for 7 weeks caused loss of TH protein in the striatum and midbrain.…”
Section: Tyrosine Hydroxylase Is Altered Upon Olfactory Mn Exposures supporting
confidence: 90%
“…First, olfactory Mn instillation significantly down-regulated TH by 78% in iron-adequate rats ( Figure 5A; P< 0.001) and by 70% in iron-deficient rats (P< 0.001; n = 4 per group), which is in agreement with Zhang et al [42], who showed that chronic manganese exposure (0.1-1 µM for 24 h) induced a dose-dependent decrease in TH activity of dopaminergic neuronal cell line. Sriram et al [43] also reported that rats exposed to aerosolized welding fumes (manual metal arc-hard surfacing; containing high Mn) of 0.5 mg/rat for 7 weeks caused loss of TH protein in the striatum and midbrain.…”
Section: Tyrosine Hydroxylase Is Altered Upon Olfactory Mn Exposures supporting
confidence: 90%
“…47 Conversely, other studies using differentiated N27 dopaminergic cells exposed to low Mn concentration did not demonstrate alteration of Ser40 phosphorylation. 49 However, Mn caused a decrease of TH activity in a manner dependent of PKCd and PP2A activity. 49 Therefore, it is evident that Mn may affect TH activity; however, the effect of Mn on TH level, activity, and phosphorylation deserves to be studied in dopaminergic neurons from intact tissue exposed in vivo in order to clarify the TH modulation in situ by Mn.…”
Section: Alteration In Mapk and Akt Signaling Induced By Manganesementioning
confidence: 96%
“…49 However, Mn caused a decrease of TH activity in a manner dependent of PKCd and PP2A activity. 49 Therefore, it is evident that Mn may affect TH activity; however, the effect of Mn on TH level, activity, and phosphorylation deserves to be studied in dopaminergic neurons from intact tissue exposed in vivo in order to clarify the TH modulation in situ by Mn. Abbreviations: CaMK, calciumand calmodulin-stimulated protein kinase; ERK, extracellular signalregulated protein kinase; MK-2, MAPK-activated protein kinase; PDPK, proline-directed protein kinase; PKA, protein kinase A; PKC, protein kinase C; PKG, protein kinase G; PP2A, protein phosphatase 2A.…”
Section: Alteration In Mapk and Akt Signaling Induced By Manganesementioning
confidence: 96%
“…In addition, abusers of the Mn-containing Bazooka (a cocaine-based drug) are also leading to Mn neurotoxicity [14]. The recent introduction of an Mn-containing fuel additive, methylcyclopentadienyl Mn tricarbonyl, to gasoline has also raised concerns over potential chronic exposures to Mn [15]. Inhaled Mn can bypass the gut and enter into the brain in two ways: by olfactory (nasal airway) neural pathways that provide a direct path to brain tissue, and by pulmonary uptake with long residence time that could provide a source of continuing exposure [16].…”
Section: Exposure To Mnmentioning
confidence: 99%
“…Adverse neurological effects of Mn also occurred in people who drank Mncontaminated water in many countries [15]. Although the World Health Organization discontinued Drinking Water Guideline [31] as 500 ug/L in 1958 and 400 ug/L in 2004, the latter guideline was criticized as still too high to adequately protect public health.…”
Section: Exposure To Mnmentioning
confidence: 99%